POLITIK HUKUM PIDANA DALAM PENANGGULANGAN TINDAK PIDANA PEMILU DEMI MEWUJUDKAN KEADILAN PEMILU - Maria Sinaga (to-ra, 2021)
This research examines the problematics of the enforcement of election criminal law as contained in Law Number 7 of 2017 concerning General Elections, with a focus on criminal policy or politics of criminal law in the context of overcoming election crimes in Indonesia. The problems of election law are not only related to regulated criminal norms, but also with the handling mechanisms and institutions involved in their enforcement. This research utilizes legal research methods with a statute approach, a case approach, and a historical approach. By applying qualitative analysis, the results of the study conclude two important things. First, there are problems in regulating election crimes as contained in Law Number 7 of 2017 concerning General Elections, namely the existence of criminalization in election crimes, the subjects of criminal law mostly target election organizers, the absence of minimum and maximum criminal sanction, and the unchanged time limit for handling election crimes at the level of investigation, prosecution and trial in court. Second, it is necessary to have a criminal policy in the context of overcoming election crimes by taking steps to improve the legal substance, legal structure, and legal culture in the administration of elections. Keywords: criminal law, election crime, election criminal law, electoral justice